Performance analysis of a combined cold and power (CCP) system with exergy recovery from LNG-regasification. (15th September 2019) - Atienza-Márquez, Antonio; Bruno, Joan Carles; Akisawa, Atsushi; Coronas, Alberto
Abstract: Liquefied Natural Gas (LNG) is becoming vital in relation to energy transition and fighting climate change. Because of its cryogenic temperature (111 K), LNG is an exergy "mine" that can be exploited in the regasification process for multiple industrial applications. But this exergy is usually wasted. This research presents a Combined Cold and Power (CCP) system with exergy recovery from LNG-regasification. This exergy is exploited for the combined production of electricity and low-temperature refrigeration distributed through a CO2 District Cooling Network. These systems entail many benefits, but also pending challenges. The CCP system is modelled using real operation data, and its performance is analyzed and benchmarked against that of a cryogenic power plant, both at design and off-design operating conditions. The proposed CCP system reports an equivalent electricity saving of 139 kWh/t-LNG with an exergetic efficiency of 40%, turning into useful energy up to 64% of the maximum cold recoverable in the regasification process. The performance enhances as the heat source temperature rises. Higher LNG flow rates contribute to increase the electricity and refrigeration production, but irreversibilities also increase. Finally, findings show that a low LNG regasification pressure is preferable in spite of the negative effect on the power generation. Highlights: A Combined Cold and Power (CCP) system with LNG exergy recovery is proposed. LNG-based CCP systems entails many benefits, but also bottlenecks to overcome. A plant regasifying 150 t-LNG/h produces 21 MW of cold and 3.36 MW of power. Up to 64% of the maximum cold available in LNG-regasification is recovered. The CCP plant boost the exergetic efficiency of a cryogenic power plant.